Peningkatan Efektivitas Sistem Insentif Pegawai Divisi Retail Banking pada Bank XY - Renny Indrawati; Parulian Hutagaol; Joko Affandi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Bank XYZ is bank that  already  launched credit card in 2007. In their operations, Bank XYZ applying the provision of insentive for the sale of a credit card with the aim that can improve employee motivation to high performing better. Basically every company hopes to reach the target of predetermined sales. But in reality the sale of a credit card to the Bank XYZ Bogor branch has not yet reached the set target. Not achieve the target that is supposed to identify that there is a problem in the achievements of employee performance whereby the employee has not been motivated to work optimally. While Bank XYZ strategy are already making the provision of incentives for retail banking staff who performs the sale of the credit card.The purpose of this research is: 1. Indentify the influence of incentives on employee motivation retail banking division in Bank XYZ in the target of credit card sales. 2. Indentify the influence of an incentive against the employee performance retail banking division. 3. Formulate efforts to improve the effectiveness of incentive system in order to increase the employee performance retail banking division. The process of data analysis begins with some of the stage where the first stage is a test of validity and reability instrument. Descriptive statistic analysis conducted to determine how perceptions of respondents to statements in the questionnaire through analysis rataan score. Through descriptive of statistical analysis can be seen how perceptions of respondents to incentives, motivation and performance. Next after the statistical analysis descriptive done testing SEM (Structural equation model) operated through the LISREL program. The results of the analysis show that the incentive effect significantly against the major motivation of employees. Motivational variables on performance demonstrates that a significant effect on performance the motivation of employees. When compared to the value of the charge factor of motivation on performance, different values looks at factors variable charge directly on performance incentives that show the influence of the small and insignificant. This incentive has the role of small shows a factor in improving the performance of staff Bank XYZ retail banking division. This is shows that employees incentive to affect the performance of retail banking division through motivation, demonstrable of indirect influence more motivation than through direct influence on the performance.